A comparison of two methods of treatment for catheter-related bloodstream infections in patients on home parenteral nutrition. Issue 5 (October 2015) - Ławiński, Michał; Majewska, Krystyna; Gradowski, Łukasz; Fołtyn, Iwona; Singer, Pierre
Summary Background & aims Home parenteral nutrition (HPN) enables patients who cannot eat normally to survive and function. Catheter-related bloodstream infections (CRBSIs) are the most dangerous complication, which may be fatal if left untreated or if treatment is delayed. For over 20 years CRBSIs were managed by catheter removal and implantation of a new one after completion of antibiotic treatment. However, frequent catheter replacements put the patient at risk of large vein thrombosis, which may render parenteral nutrition impossible. The management of CRBSIs evolved into antibiotic treatment without catheter removal. The effectiveness of this approach was, however, limited by the low penetration of the antibiotics into the biofilm. Filling catheters with concentrated ethanol destroys the biofilm and does not result in the emergence of drug resistance. The aim of our study was to assess the remote outcomes of CRBSI treatment using two approaches: antibiotic-ethanol lock therapy and catheter replacement. Methods: We retrospectively analysed the treatment outcomes of CRBSI diagnosed and managed in HPN patients. During the analysed period, a total of 428 patients between 13 and 96 years of age were on HPN and a total of 181 of them suffered a total of 352 CRBSI episodes managed with one of the two approaches. Results We showed no significant differences between the two approaches in terms of survival likelihood or duration of catheter use after an episode of CRBSI caused by various bacterial species. Conclusion The use of antibiotic-ethanol lock therapy in the management of CRBSI is equally effective as catheter replacement.